Untreated depression and anxiety in patients with common skin diseases: a cross-sectional study in China - Tang, Tao-Ran; Wang, Mi; Li, Hong; Yang, Song-Chun; Zhang, Cheng-Cheng; Lin, Wen-Rui; Ke, Xin-Chen; Zhang, Han-Yi; Su, Juan; Zhu, Shi-Lin (Frontiers in Psychology, 2023)
Objective The study aimed to analyze the current status and reasons for the neglect of the psychological need of patients with common skin diseases. Methods This cross-sectional study was conducted in China using an online self-assessment questionnaire distributed via social media. Demographic, clinical and psychological data were collected, and the main outcomes, i.e., depression (evaluated using the 9-item Patient Health Questionnaire, PHQ-9) and anxiety (evaluated using Generalized Anxiety Disorder-7, GAD-7). Multivariate regression analysis was used for the prediction of variates of mental health service seeking behaviors. Results A total of 1,010 patients participated in the survey, and 273 (27.0%) patients met the “with need” criteria, i.e., having the need for mental health intervention but not being treated. In the multivariate regression model, income (OR = 0.80, 95%CI: 0.65–0.99), duration of disease (OR = 0.68, 95%CI: 0.49–0.95) and suicide ideation (OR = 2.10, 95%CI: 1.14–3.87) were significant factors. For patients who did not receive mental health care, the lack of knowledge about the availability of mental health services, lack of knowledge of where to seek help, concerns about the side effects of treatment, failure to seek treatment for severe skin diseases, and absence of current psychological distress were associated with their need for psychological intervention. Conclusion This study examined the current status of the need for psychological intervention and the reasons why the need was unmet in patients with skin diseases. Due to the confusion and a lack of knowledge about their mental health issues, mental health services are often underutilized.